Perspectives of stakeholders on barriers to COVID-19 protective behaviors adherence and vaccination among Myanmar migrant workers in southern Thailand: A qualitative study - Hein Htet; Wit Wichaidit; Aungkana Chuaychai; Tiida Sottiyotin; Kyaw Ko Ko Htet; Hutcha Sriplung; Virasakdi Chongsuvivatwong (PLoS ONE, 2025)
Studies have been conducted on migrant health during the COVID-19 pandemic. However, in-depth information is scarce regarding the barriers to preventing COVID-19 in this vulnerable population. The objective of the study is to explore the barriers to COVID-19 protective behaviors adherence and vaccination among Myanmar migrant workers in Thailand. We conducted an interview-based qualitative study among 7 migrants from Myanmar, 6 Thai employers, and 9 Thai healthcare providers in the cities of Hat Yai and Pattani in Southern Thailand. We recruited participants by purposive sampling. We conducted in-depth interviews in-person or via telephone in Thai or Burmese language, transcribed the interview, and conducted thematic analysis. Regarding adherence to COVID-19 protective behaviors, two themes emerged: lifestyle and habit-related barriers, and non-vaccine supply chain management barriers. Regarding COVID-19 vaccination, three common themes emerged: fear, barriers related to health education and health promotion, and vaccine supply chain management. Supply chain management was a common theme in both domains. However, each domain also had additional themes. Our study contributed empirical findings that could be of interest to stakeholders in migrant health. However, limitations regarding the generalizability of the findings and social desirability should be considered in the interpretation of the findings.